Determinasi Kepemimpinan Berlandaskan Nilai-Nilai Tri Hita Karana Terhadap Kinerja Guru Di Kecamatan Buleleng - I Made Sedana (Purwadita : Jurnal Agama dan Budaya, 2021)
This study aims to determine the magnitude of the contribution of the principal's leadership variable based on the values of Tri Hita Karana and organizational culture to teacher performance. This type of research is ex-post facto with multiple linear regression analysis design. The population in this study were 40 people. The entire population was used as a research sample so that this study included a population study. Collecting data using a questionnaire about the principal's leadership variables based on the values of Tri Hita Karana, and organizational culture and teacher performance. The results showed that (1) there was a contribution of principal leadership based on the values of Tri Hita Karana to teacher performance of 15.48% (2) there was a contribution of school organizational culture to teacher performance of 14.57%; (3) there is a simultaneous contribution between the principal's leadership based on the values of Tri Hita Karana and organizational culture on teacher performance of 30.05%.